Age of Iron: Adaptation and the Matter of Troy in Clements’s Indigenous Urban Drama - Rabillard, Sheila (Theatre Research in Canada / Recherches théâtrales au Canada, 2010)
In Age of Iron, Clements freely adapts Euripides’s Trojan Women. In Hutcheon’s terms, she "indigenizes," drawing on the ancient play selectively and localizing it. Her localization is unusual because she creates a double setting and a palimpsest of Trojan and Indigenous referents. The action occurs in a place which is both contemporary Vancouver and ancient Troy; the fall of Troy is also the conquest of BC’s Aboriginal peoples. This duality allows Clements to lament historical suffering even as she insists that conquest is happening now on the streets of Vancouver. The superimposition of different frames of reference politicizes the gesture of adaptation: Clements’s transformative art implies that past patterns of oppression can be re-shaped. Yet adaptation of a classical text is an ironic gesture, given that the play stages the destructive imposition of European culture. The layered ironies of the play derive, as well, from Clements’s appropriation of the "matter of Troy." Exposing the instability of national mythologies, she rejects the mythic descent of Britons from exiled Trojans, and claims Troy for her Aboriginal-identified characters. She revises British triumphalism, and instead of prophesying Troy reborn uses setting, set, and performance to dramatize the exilic present of "Trojans" in their homeland. Résumé Dans sa pièce Age of Iron, Clements s’inspire librement des Troyennes d’Euripide. Pour citer Hutcheon, elle «. indigénise. » la pièce, en s’en inspirant sélectivement et en la localisant. Le procédé de localisation qu’elle emploie est inhabituel puisque Clements crée un double espace et un palimpseste de référents troyens et indigènes. L’action se déroule dans un lieu qui est à la fois le Vancouver d’aujourd’hui et l’ancienne Troie; la chute de Troie, c’est aussi la conquête des peuples autochtones de la Colombie-Britannique. Cette dualité permet à Clements d’évoquer la souffrance historique alors même qu’elle insiste sur le fait que la conquête se déroule aujourd’hui dans les rues de Vancouver. La surim-position de cadres de référence fait de cette adaptation un geste politique.: l’art de transformation pratiqué par Clements laisse entendre qu’on peut remodeler les anciennes formes d’oppression. Pourtant, adapter ce texte classique, c’est poser un geste empreint d’ironie.: la pièce met en scène l’imposition destructive de la culture européenne. Les multiples niveaux d’ironie de la pièce découlent aussi de l’appropriation que fait Clements de l’«.affaire de Troie.». Exposant l’instabilité des mythologies nationales, elle rejette l’origine mythique des Britanniques, supposés descendants de Troyens exilés, et réclame Troie pour ses personnages identifiés comme étant Autochtones. Elle revoit le triomphe britannique et, plutôt que de prophétiser sur la renaissance de Troie, elle se sert du lieu, du décor et du jeu pour donner une forme dramatique à la présence exilique des Troyens dans leur patrie.